The Conceptualization of Space: Places in Signed Language Discourse - Wilcox, Sherman (Front Psychol, 2020)
We examine the conceptualization of space in signed language discourse within the theory of cognitive grammar. Adopting a Places view, we define Place as a symbolic structure that associates a schematic semantic pole and a schematic phonological pole. Places acquire full contextual meaning and a specific spatial location in the context of a usage event. In the present article, we analyze the referential function of Places in different grammatical constructions throughout a selection of videos produced by deaf Argentine Sign Language signers. Our analysis examines Places, which are associated with entities in the surrounding spatial environment as well as Places that are created or recruited in discourse without reference to surrounding physical entities. We observe that Places are used in pointing, placing, and other grammatical constructions in order to introduce and track referents in ongoing discourse. We also examine the use of conceptual reference points, by which Places afford mental access to new related concepts that are the intended focus of attention. These results allow us to discuss three related issues. First, for signed language discourse, space is both semantically and phonologically loaded. Signers’ semantic and phonological choices for Place symbolic structures are motivated by embodied experience and the abstraction of usage events. Second, Places occur along a continuum from deixis to anaphor, united by the same conceptual system and differing in extent of phonological subjectification. Third, we suggest developmental implications of our Place analysis.